Suitability Level Analysis of Google Map’s Travel Time and Traffic Density Classification - Laksita Amelia Paramesti; Dedi Atunggal (Jurnal Geospasial Indonesia, 2019)
Traffic congestion is one of problem that occur in big cities, therefore people need traffic information to determine traffic condition. One of many applications that provides traffic information is Google Maps. From the information generated, there are insuitability between google maps’s traffic update and travel time with the actual condition. So the aim of this study is to analyze the suitability level of traffic density classification and google maps travel time. Based on the speed range by Google, the level of suitability can be determined, while the google maps travel time is done by statistical tests. The statistical test used is a statistical test of two parameters using table t with 95% confidence level. The results of this study indicate that the level of suitability of the traffic classification only reaches 35%. The low level of suitability is caused by network latency. While information on google maps travel time does not have a significant difference in actual time.